Demystifying the mesiobuccal root of maxillary first molar using cone-beam computed tomography - P Karunakar; Raji V Solomon; Chaitanya Byragoni; Lakshmi Sanjana; G Komali (Wolters Kluwer Medknow Publications, 2015)
Context: Imaging techniques and endodontics are inseparable from each other as the former have always been the cornerstone for successful endodontic diagnosis and treatment. Aims: The objective of this study was to detect the presence of extra canals in the mesiobuccal root of the maxillary first molar using cone-beam computed tomography (CBCT). Materials and Methods: In this study, 75 freshly extracted human maxillary first molars were mounted on arches and exposed to CBCT and digital radiography (control). The incidence of additional canals is then evaluated using CBCT and the teeth identified with additional canals were marked and again exposed to RVG. Statistical Analysis Used: The results were analyzed by three examiners two endodontists and an oral radiologist to eliminate bias. Inter and intra rater agreement was analyzed using the kappa coefficient. Results: Statistical analysis revealed the incidence of extra canals to be at 47.1% with the difference between the readings of the 3 examiners being statistically insignificant. Conclusions: CBCT can be considered an advanced diagnostic tool for primary and secondary endodontic treatments.